Higher-Order Beliefs and Risky Asset Holdings - Yuriy Gorodnichenko; Xiao Yin (Institute of Labor Economics (IZA), 2024)
We combine a customized survey and randomized controlled trial (RCT) to study the effect of higher-order beliefs on U.S. retail investors' portfolio allocations. We find that investors' higher-order beliefs about stock market returns are correlated with but distinct from their first-order beliefs. Furthermore, the differences between the two vary systematically according to investor characteristics. We use information treatments in the RCT to create exogenous differential variations in first- and higher-order beliefs. We find that an exogenous increase in first-order beliefs increases the portfolio share allocated to the stock market (risky assets), while an exogenous increase in higher-order beliefs reduces it.
Keywords: G11; G12; G51; D84; C83; 330; expectations; surveys; higher-order beliefs; asset pricing